2020
DOI: 10.3390/ma13184091
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on 3D Printing of Automatically Designed Customized Wrist-Hand Orthoses

Abstract: The paper presents results of research conducted on a batch of additively manufactured individualized openwork wrist–hand orthoses made of thermoplastics and designed automatically based on 3D-scanned geometry of a given patient. The aim of the work was to establish an automated design process and find a reliable set of parameters for rapid and affordable manufacturing of usable orthoses on popular 3D printers, with little or no supervision of the process. The paper presents motivations, methodology of automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 26 publications
(38 reference statements)
0
61
0
Order By: Relevance
“…We view our results as preliminary. They lead to further implications: in the broadest context, CI-based optimization of 3D printing processes within the Industry 4.0 paradigm is possible [ 68 ]. This requires not only efficient technical solutions, but also correct consumer behavior and attitudes toward the mentioned waste management [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…We view our results as preliminary. They lead to further implications: in the broadest context, CI-based optimization of 3D printing processes within the Industry 4.0 paradigm is possible [ 68 ]. This requires not only efficient technical solutions, but also correct consumer behavior and attitudes toward the mentioned waste management [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The system, abbreviated AutoMedPrint (automated 3D printing of medical products), has a task of automated design and production preparation of individualized orthopedic supplies—mainly limb orthoses and upper-limb prostheses. The system’s concept is described in the authors’ earlier works [ 30 , 31 ], and its use is presented in Figure 2 , while a flow graph of working with the system is presented in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In general, an intelligent CAD model can be regarded as one that is automatically updated on the basis of knowledge description stored in an external file (a so-called design table) [ 32 ]; such models are frequently used for mass customization purposes. The intelligent model was made by the authors, implementing methodologies shown in previous studies [ 30 , 31 , 33 ] and also using the approach presented in [ 34 ]. The complete prosthesis is a modular one, intended for use by children in daily situations; the hand could be either mechanical (a rotary grip for driving a bike or a scooter) or cosmetic (prosthetic hand).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no significant difference in the performance of the task; whether an assistive device was worn, did not affect the actual performance. In contrast, 3D printing applied on orthoses have been introduced in papers by Górski et al [20]. However, the parametric 3D hand model proposed by this study allow quick generation of 3D hand geometry approximating to a user's actual hand.…”
Section: Questionnaire Integrationmentioning
confidence: 98%